Short interfering RNA in cancer therapy - Majorek, Maria; Guzenda, Piotr; Lamparska-Przybysz, Monika; Wieczorek, Maciej (Contemporary Oncology/Współczesna Onkologia, 2006)
y the results of cancer treatment are still disappointing. Genetic engineering brings new hopes and capability of interference in the genome of tumour cells for regulation of function of genes responsible for transformation and progression of cancer. Discovery of the phenomenon of interference RNA has initiated research by using small interfering RNA (siRNA) for gene silencing in mammalian cells. Natural occurrence of this phenomenon in eukaryotic organisms provides the greatest efficiency and specificity in comparison with other methods of gene silencing such as antisense oligonucleotides and ribozymes. Despite the existence of technical challenges related to specificity, synthesis and feeding siRNA, this molecule has great therapeutic capabilities in treatment of such complicated sickness as advanced tumours.